2014
DOI: 10.1093/ejcts/ezu318
|View full text |Cite|
|
Sign up to set email alerts
|

Functional results after chest wall stabilization with a new screwless fixation device

Abstract: Our results suggest that stabilization of the chest wall with this screwless rib fixation device can be performed with a low morbidity and lead to early restoration of chest wall integrity and respiratory pump function, without clinically relevant functional restriction. Owing to the simplicity of the fixation technique, indications for stabilization can be safely enlarged to selected patients with dislocated and painful rib fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 21 publications
0
15
0
7
Order By: Relevance
“…In our study, 2 patients did not undergo complete hardware removal. Wiese et al (6) also demonstrated suitable outcomes in 2 patients who underwent partial removal. We advocate that if hardware must be removed early, then partial hardware removal may be a suitable option.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In our study, 2 patients did not undergo complete hardware removal. Wiese et al (6) also demonstrated suitable outcomes in 2 patients who underwent partial removal. We advocate that if hardware must be removed early, then partial hardware removal may be a suitable option.…”
Section: Discussionmentioning
confidence: 91%
“…Rib fractures are rarely open fractures, but they do often communicate with the airways (via pulmonary lacerations) or with the environment (via TT), and therefore patients with SSRF may be at increased risk for infection. Wiese et al (6) reported on 2 patients with hardware infection after SSRF; both had diabetes mellitus and had sustained severe trauma with extensive soft-tissue contusions. Bacterial translocation from TTs placed before SSRF has been suggested as a mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clamp systems are managed through similar approaches as the rib plates. They encompass the rib and generally require slightly extended intercostal dissection, which is not generally associated with a higher risk of a lesion of intercostal vessels or nerves, but the biomechanical properties are based on a different principle from that of the locked plate osteosynthesis with a considerable risc of implant failure (24,25). A retrosternal metal bar, as is very well known from the minimized pectus excavatum reconstructions according to Nuss, can also effect stabilization of the chest wall in certain cases.…”
Section: Discussionmentioning
confidence: 99%